2021
DOI: 10.1101/2021.06.08.447604
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of subcellular transcriptomes by RNA proximity labeling with Halo-seq

Abstract: Thousands of RNA species display nonuniform distribution within cells. However, quantification of the spatial patterns adopted by individual RNAs remains difficult, in part by a lack of quantitative tools for subcellular transcriptome analysis. In this study, we describe an RNA proximity labeling method that facilitates the quantification of subcellular RNA populations with high spatial specificity. This method, termed Halo-seq, pairs a light-activatable, radical generating small molecule with highly efficient… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…The H2A–H2B dimer was not previously predicted and was only identified based on the cryo-EM density. In support of our identification, recent RNA proximity labelling studies show that hTR is enriched in histone H2B pulldown [ 80 ]. The P6.1 stem of the CR4/5 is highly conserved among vertebrates and essential for telomerase catalytic activity [ 29 , 81 ].…”
Section: Progresssupporting
confidence: 88%
“…The H2A–H2B dimer was not previously predicted and was only identified based on the cryo-EM density. In support of our identification, recent RNA proximity labelling studies show that hTR is enriched in histone H2B pulldown [ 80 ]. The P6.1 stem of the CR4/5 is highly conserved among vertebrates and essential for telomerase catalytic activity [ 29 , 81 ].…”
Section: Progresssupporting
confidence: 88%
“…The authors also showed that dynamic changes in RNA localization could be investigated using Halo-seq. [83] Figure 6. Dibromofluorescein (DBF)-dependent RNA and protein oxidation with subsequent propargyl amine labeling.…”
Section: Photoactivated Pl Strategiesmentioning
confidence: 99%